PENGARUH EFIKASI DIRI TERHADAP BURNOUT DAN PERBEDAANNYA BERDASARKAN GENDER - Sarah Ulfa; Melani Aprianti (Department of Islamic Psychology, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
This study aims to provide empirical evidence about the effects of Self Efficacy on Burnout. This study also wants to prove the difference level of Burnout based on Gender. The research data is the primary data that are obtained through the distribution of questionnaires to the respondents. The respondents were selected by using disproportionate stratified random sampling method. This study uses a quantitative method with 212 respondents which are students of faculty of psychology in X University Jakarta. Hypothesis testing using simple regression test and independent sample T test. The results revealed that Self Efficacy have positive effect on Burnout. Differences in burnout based on gender can not be proven through the results of this study.